A evolução dos possíveis e a construção do conhecimento lógico-matemático via jogo de regras em alunos com dificuldades de aprendizagem - Reisdoefer, Deise Nivea (2006)
This research aimed to study the evolution of possible and the construction of the logical-mathematical knowledge through rules games with elementary students, 5th and 6th degrees. The leading questions were: Have they difficulty at learning Mathematics? Do they manage the four basic operations? Do rules game helps the evolution of possible and the construction of the logical-mathematical knowledge? As theoretical reference were used works from Piaget (1972a, 1972b, 1973, 1977, 1985, 1996, 1998), Grando (1995, 2000), Macedo (1992, 1997, 2005a, 2005b), Brenelli (1996), Piantavini (1999) and Ciasca (1994, 2003). The general objective was to show that rule game contributes for the evolution of possible and the construction of the logical-mathematical knowledge. The specific objectives were to identify the operation level, of possible and mathematical knowledge of the research subjects; to realize the educative intervention based on rule games; to show the construction process of logical-mathematical knowledge and the evolution of possible. The methodology used was a case study focused on Piaget´s clinical method. The research was done with seven boys, 12 years old, studying 5th and 6th degree in a public school. Procedures of data collect were: registration on the field diary, movie making, observation and educative intervention with rule games as Mathematical Detective (REISDOEFER, 1999) and Contig 60® (REGATO, 1980, 1986). Analysis and discussion of the data were based on Piaget´s epistemological theory. The results showed that: students had difficulty with four basic mathematical operations, mainly division; they had different operation levels and of possible; the rule games used were efficient for the mathematical learning; it was showed great interest on learning by games, social interaction, evolution of the four basic operation learning and raising of new possible and rules. It was brought to a conclusion that using rule games helped the evolution process of possible and the construction of logical-mathematical knowledge; transcended the game representation as a resource to motivation and fixation of contents; propitiated action, integration, reflection and transposition of learning difficulties, contributing for social inclusion. Keywords: teaching-learning; games; Piaget; logical-mathematical knowledge; level